Kualitas Pembinaan dan Pengawasan Narapidana di Rutan Kelas IIB Maumere - Mariana Agneta Diana Dea; I Nyoman Subanda; Ni Ketut Arniti; Sahri Aflah Ramadiansyah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The coaching and supervision of inmates is an integral part of the correctional system which aims to shape the behavior of inmates so that they are able to reintegrate socially while still upholding Human Rights (HAM). This study aims to examine the quality of coaching and supervision of inmates at the Class IIB Maumere State Prison (Rutan), especially in its implementation according to modern correctional principles. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, direct observations, and documentation studies. The results of the study show that the implementation of coaching and supervision has been carried out in accordance with the provisions of the applicable laws and regulations, but it has not run optimally. The main obstacles include limited human resources, inadequate facilities and infrastructure, and the implementation of a humanist approach in fostering assisted residents. In addition, coordination between officers still needs to be improved so that the coaching program runs more effectively. Therefore, it is necessary to strengthen correctional management, increase the capacity and professionalism of officers, and support adequate facilities to realize effective, humane, and fair coaching and supervision.